2006
DOI: 10.2341/05-53
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Adhesive Systems on Interfacial Dentin Gap Formation In Vitro

Abstract: The thickness of the smear layer did not influence the mean gap width (p>0.05). The etch & rinse systems showed the lowest mean IGW in the 1-day group. Their IGW remained unchanged after 6 months. The self-etch systems showed wider initial IGW, which diminished after 6 months water storage, to sizes similar to the etch & rinse systems. The hybrid layer was thicker when bonded to #60 SiC-treated dentin; however, this difference was only statistically different for the 3-step etch & rinse system (p=0.001). The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 31 publications
1
49
1
Order By: Relevance
“…5). These findings were consistent with those of previous studies, which reported that resin tags made only a minor contribution to bond strength 7,31,32) . As a result, the shear bond strengths obtained with Clearfil SE Bond were statistically similar (p=0.076) to those obtained with Solobond Plus in this study.…”
Section: Discussionsupporting
confidence: 83%
“…5). These findings were consistent with those of previous studies, which reported that resin tags made only a minor contribution to bond strength 7,31,32) . As a result, the shear bond strengths obtained with Clearfil SE Bond were statistically similar (p=0.076) to those obtained with Solobond Plus in this study.…”
Section: Discussionsupporting
confidence: 83%
“…The area of these sections was calculated based on their width and length. 21 The sum of all stick sections, divided by the total length of the interface, resulted in the mean stick gap width. The mean gap width of the individual tooth sections was than calculated.…”
Section: Gap Width Measurementmentioning
confidence: 99%
“…27 Furthermore, in a study carried out by Yazici and others, 30 the Er,Cr:YSGG laser-prepared cavities exhibited the same amount of microleakage as that with bur-prepared cavities with etch-and-rinse and single-step self-etch adhesive systems in Class V composite resin restorations. In another study, no significant differences were observed in the cementum microleakage of bur-and laser-prepared Class V cavities in nanorestorative materials.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the effect of acidity of self-etch systems and hybrid layer thickness formed by these adhesives on interfacial dentin gap formation, 27 it is suggested that the effect of hybrid layer thickness and pH of different self-etch adhesive systems on marginal gap formation in laser-prepared cavities be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation